Jacques Pierre Brissot in America and France, 1788-1793 : in search of better worlds - Oliver, Bette Wyn, 1933- (Lexington Books, 2016)
This book examines a decisive five-year period in the life of Jacques Pierre Brissot, one of the influential leaders of the French Revolution. An idealistic, somewhat naive journalist who became a member of the national assembly, Brissot championed the new American republic as an example for the French revolutionary government to follow. This book is not intended to serve as a biography of the Girondin leader, but rather to present an examination of his life between 1788, when he visited the United States, and 1793, when he was executed. As such, the narrative necessarily focuses on the events of the revolution as the ever-present background to Brissot's thoughts and actions. Both as a journalist and as a legislator, Brissot was consumed by the tumultuous events of the period under review. The book is based primarily on the publications, correspondence, and memoirs of Brissot, as well as materials from the Bibliotheque Nationale, the Archives Nationales, and relevant secondary sources. It also includes comparisons between Brissot's observations of America in 1788, published in 1791 as 'Nouveau Voyage dans les Etats-Unis de l'Amerique Septentrionale, 1788,' and those of his countryman Alexis de Tocqueville in his widely read 'Democracy in America, ' which described his visit in 1831 and was published in 1835.